Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3389/fmicb.2018.01761
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ExeM, an Extracellular Nuclease of Shewanella oneidensis MR-1

Abstract: Bacterial extracellular nucleases have multiple functions in processes as diverse as nutrient acquisition, natural transformation, biofilm formation, or defense against neutrophil extracellular traps (NETs). Here we explored the properties of ExeM in Shewanella oneidensis MR-1, an extracellular nuclease, which is widely conserved among species of Shewanella, Vibrio, Aeromonas, and others. In S. oneidensis, ExeM is crucial for normal biofilm formation. In vitro activity measurements on heterologously produced E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 65 publications
(110 reference statements)
0
13
0
Order By: Relevance
“…Although DNA and lipids are energy-rich and abundant in marine sediments [ 9 ], the identity and distribution of nucleases and lipases across genomes, organisms and databases is not well characterized, in contrast to the enzymes involved in the breakdown of proteins [ 92 , 93 ] and polysaccharides [ 94 , 95 ]. Few studies have identified bacterial extracellular nucleases [ 96 , 97 ] and lipases [ 98 ] associated with catabolic activities. Furthermore, nucleases and lipases can also participate in synthesis and salvage pathways, and are not necessarily involved in catabolism [ 99 , 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although DNA and lipids are energy-rich and abundant in marine sediments [ 9 ], the identity and distribution of nucleases and lipases across genomes, organisms and databases is not well characterized, in contrast to the enzymes involved in the breakdown of proteins [ 92 , 93 ] and polysaccharides [ 94 , 95 ]. Few studies have identified bacterial extracellular nucleases [ 96 , 97 ] and lipases [ 98 ] associated with catabolic activities. Furthermore, nucleases and lipases can also participate in synthesis and salvage pathways, and are not necessarily involved in catabolism [ 99 , 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced DNAse activities observed in OMVs from post-spaceflight re-isolates correlated with a poor biofilm production in parental bacteria, when the activity of such nucleases was demonstrated to balance the extent of biofilm formation, and this is congruent with the previously published results by Sharma and Singh (2018) . Nucleases also contribute to the lower bacterial transformation capability of different bacteria, preventing horizontal gene transfer ( Binnenkade et al, 2018 ; Jhelum et al, 2018 ). The nuclease-associated OMVs of the dominant KMC K. intermedius can be represented as safeguards, keeping the essential genome stability in this microecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with a previous report (Seper et al, 2011), the nuclease assay used herein confirmed that Xds has exonuclease activity only capable of degrading linear DNA but not circular DNA. In contrast ExeM of Shewanella oneidensis , a homolog of Xds with 41% identity, was recently characterized to have sugar-unspecific endonuclease activity (Binnenkade et al, 2018). With 94.3 kDa Xds represents a relatively high molecular weight multi-domain enzyme.…”
Section: Discussionmentioning
confidence: 99%